Condições de trabalho e saúde psíquica dos trabalhadores de saneamento básico na região metropolitana de Belo Horizonte - Magda Rocha Vaz Tertuliano (2018)
I planned with this research to identify the perception of basic sanitation workers about working conditions and to analyze how these relate to their psychic health in a basic sanitation company in the state of Minas Gerais. I investigated the operational and commercial positions in the areas of greater concentration of workers of a state-owned mixed-economy company in the metropolitan region of Belo Horizonte. I referred the concepts of psychic health and working conditions to in psycho-sociology as multidimensional. To collect data on working conditions and to evaluate the psychic health of employees, I used the following instruments: Socio-occupational form, Work Condition Questionnaire (QCT), General Health Questionnaire (QSG-12), Self-esteem Scale of Rosemberg and Affective Welfare Scale at Work. I developed descriptive and inferential statistical analyzes to systematize participants' answers and achieve the research objectives. I used the software Statistical Package of Social Science (SPSS). I identified five profiles of psychic health: Affective, Optimistic, Satisfied, Pessimistic and Dissatisfied. The first two presented the most balanced indicators, but the last three drew attention to the unbalances found. I found that various aspects of working conditions differentiate psychic health profiles, such: working time, pain / discomfort in the body, withdrawal, perceived risk of accidents and illness, qualification requirements, and lack of support in the execution the task. The specificities found in the basic sanitation category indicate actions to prevent and promote health and safety at work besides new studies to elucidate other forms of working conditions and relation with the psychic health.